Future options for ALK-positive non-small cell lung cancer. Issue 3 (March 2015) - Iacono, Daniela; Chiari, Rita; Metro, Giulio; Bennati, Chiara; Bellezza, Guido; Cenci, Matteo; Ricciuti, Biagio; Sidoni, Angelo; Baglivo, Sara; Minotti, Vincenzo; Crinò, Lucio
Highlights Crizotinib and ceritinib are highly effective ALK-TKIs for ALK-rearranged NSCLC. Assays other than FISH (IHC, RT-PCR) are being investigated for ALK testing. Next-generation ALK-TKIs are predicted to overcome resistance to crizotinib. Combination of targeted therapies hold out much promise for ALK-positive NSCLC.